Early changes in arbuscular mycorrhiza development in sugarcane under two harvest management systems - Azevedo,Lucas Carvalho Basilio de (2014)
Sugarcane (Saccharum spp.) is grown on over 8 million ha in Brazil and is used to produce ethanol and sugar. Some sugarcane fields are burned to facilitate harvesting, which can affect the soil microbial community. However, whether sugarcane pre-harvest burning affects the community of arbuscular mycorrhizal fungi (AMF) and symbioses development is not known. In this study, we investigated the early impacts of harvest management on AMF spore communities and root colonization in three sugarcane varieties, under two harvest management systems (no-burning and pre-harvest burning). Soil and root samples were collected in the field after the first harvest of sugarcane varieties SP813250, SP801842, and RB72454, and AMF species were identified based on spore morphology. Diversity indices were determined based on spore populations and root colonization determined as an indicator of symbioses development. Based on the diversity indices, spore number and species occurrence in soil, no significant differences were observed among the AMF communities, regardless of harvest management type, sugarcane variety or interactions between harvest management type and sugarcane variety. However, mycorrhiza development was stimulated in sugarcane under the no-burning management system. Our data suggest that the sugarcane harvest management system may cause early changes in arbuscular mycorrhiza development.